Structure of thaumatin under acidic conditions: Structural insight into the conformations in lysine residues responsible for maintaining the sweetness after heat-treatment. (30th September 2022) - Masuda, Tetsuya; Okubo, Kyohei; Baba, Seiki; Suzuki, Mamoru; Tani, Fumito; Yamasaki, Masayuki; Mikami, Bunzo
Highlights: Structure of thaumatin under acidic conditions (pH 4.0) was determined. At pH 4.0, the Tm of thaumatin was substantially lower than that at pH 6.0. Relative B -factor values illustrate the changes in structural features due to a pH change. The reduction in relative flexibility might play an important role in preventing thermal aggregation. Abstract: Thaumatin is an intensely sweet-tasting protein. Its sweetness persists when heated under acidic conditions, but disappears when heated at a pH above 7.0. To clarify how the structural features of thaumatin resist insoluble aggregation during heating under acidic conditions, we analysed its crystal structure obtained at pH 4.0, 6.0, and 8.0. Simultaneously, the melting temperature ( Tm ) at these pH levels was determined using differential scanning fluorimetry. At pH 4.0, the Tm of thaumatin was substantially lower and the overall B -factor value of its structure was higher than those at pH 6.0. Interestingly, the relative B -factor values for most lysine residues decreased as the pH reduced. These results suggest that the overall structure at pH 4.0 becomes flexible but the relative flexibility of some regions is lower than that at pH 6.0. Thus, the reduction in relative flexibility might play an important role in preventing thermal aggregation, thereby maintaining the sweetness.